Beauty Care Ingredients Used at Kraton Yogyakarta Hadiningrat, Indonesia - Annisa Wiweka Utami; Ardyan Pramudya Kurniawan (Jurnal Biologi Tropis, 2023)
Kraton Yogyakarta Hadiningrat has a culture of beauty treatments. Knowledge of traditional beauty treatments is one of the manifestations of culture that has been passed down from generation to generation and has been used in everyday life.  This study aims to examine plants used as beauty care ingredients at Kraton Yogyakarta Hadiningrat. This research was carried out in November 2022 - July 2023 in the complex environment of Kraton Yogyakarta Hadiningrat. The methods used are semi-structured interview method (open-ended interview) and literature study of manuscript manuscripts of Traditional Jamu Records at Kraton Yogyakarta. The results of the study found 25 herbal preparations used for beauty treatments consisting of four types, namely body skin care (6 concotion), facial skin care (10 concotion), hair care (7 concotion), and reproducive organ care (2 concotion). From the results of the study it was concluded that the use of herbs for body beauty care is still used today.